Structural, functional, and bioinformatics studies reveal a new snake venom homologue phospholipase A(2) class - dos Santos, Juliana I. [UNESP]; Cintra-Francischinelli, Mariana; Borges, Rafael J. [UNESP]; Fernandes, Carlos A. H. [UNESP]; Pizzo, Paola; Cintra, Adelia C. O.; Braz, Antonio S. K. [UNESP]; Soares, Andreimar M.; Fontes, Marcos R. M. [UNESP] (Wiley-Blackwell, 2011)
Phospholipases A(2) (PLA(2)s) are enzymes responsible for membrane disruption through Ca2+-dependent hydrolysis of phospholipids. Lys49-PLA(2)s are well-characterized homologue PLA(2)s that do not show catalytic activity but can exert a pronounced local myotoxic effect. These homologue PLA(2)s were first believed to present residual catalytic activity but experiments with a recombinant toxin show they are incapable of catalysis. Herein, we present a new homologue Asp49-PLA(2) (BthTX-II) that is also able to exert muscle damage. This toxin was isolated in 1992 and characterized as presenting very low catalytic activity. Interestingly, this myotoxic homologue Asp49-PLA(2) conserves all the residues responsible for Ca2+ coordination and of the catalytic network, features thought to be fundamental for PLA(2) enzymatic activity. Previous crystallographic studies of apo BthTX-II suggested this toxin could be catalytically inactive since a distortion in the calcium binding loop was observed. In this article, we show BthTX-II is not catalytic based on an in vitro cell viability assay and time-lapse experiments on C2C12 myotube cell cultures, X-ray crystallography and phylogenetic studies. Cell culture experiments show that BthTX-II is devoid of catalytic activity, as already observed for Lys49-PLA(2)s. Crystallographic studies of the complex BthTX-II/Ca2+ show that the distortion of the calcium binding loop is still present and impairs ion coordination even though Ca2+ are found interacting with other regions of the protein. Phylogenetic studies demonstrate that BthTX-II is more phylogenetically related to Lys49-PLA(2)s than to other Asp49-PLA(2)s, thus allowing Crotalinae subfamily PLA(2)s to be classified into two main branches: a catalytic and a myotoxic one. Proteins 2011; 79: 61-78. (C) 2010 Wiley-Liss, Inc.
Keywords: phospholipase A(2); myotoxin; X-ray crystallography; phylogenetic analysis; myotube cell culture; calcium imaging